[Clinical practice guidelines for the management of chronic kidney disease stages 3b, 4 and 5 in the Peruvian Health Social Security] - Bravo-Zúñiga , Jessica (2023)
Introduction: This article summarizes the clinical practice guideline (CPG) for the management of stage 3b, 4, and 5 chronic kidney disease (CKD) in the Social Security of Peru (EsSalud). Objective: To provide evidence-based clinical recommendations for the management of stage 3b, 4, and 5 CKD in EsSalud. Methods: A guideline development group (GDG) was formed, including specialists and methodologists. The GDG formulated 9 clinical questions. Systematic searches for systematic reviews and primary studies were conducted in PubMed from December 2020 to August 2021. Evidence was selected to answer the clinical questions posed. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. The GDG used the GRADE methodology to review the evidence and formulate recommendations, points of good clinical practice (GPC), and management flowcharts. Finally, the CPG was approved with Resolution No. 88-IETSI-ESSALUD-2021. Results: This CPG addressed 9 clinical questions. Based on these questions, 17 recommendations (7 strong and 10 conditional), 28 GPC points, and 4 management flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions of the CPG for the management of stage 3b, 4, and 5 CKD in EsSalud.